Methodological Challenges in Developmental Human Behavioral Epigenetics: Insights Into Study Design - Provenzi, Livio; Brambilla, Maddalena; Borgatti, Renato; Montirosso, Rosario (Frontiers in Behavioral Neuroscience, 2018)
Developmental human behavioral epigenetics (DHBE) holds the potential to contribute to a better understanding of how early life exposures contribute to human developmental trajectories and to inform clinical practice and early interventions. Nonetheless, DHBE research to date is challenged by two major issues: (a) the frequent use of retrospective study designs; (b) the major focus on epigenetic variations associated with early life adversities, rather than protective care exposures. In order for DHBE research to maintain its promises, these issues need to be addressed in a systematic way according to a careful methodological planning of study design. In this contribution, we provide pragmatic insights on methodological aspects that should be dealt with while designing DHBE studies. We propose different study designs for the retrospective and prospective investigation of both adversity- and care-related epigenetic variations. Examples from literature are provided to better describe the advantages and the limitations of each study design.